PENGARUH PENAMBAHAN SERAT KAWAT BENDRAT TERHADAP KUAT TEKAN DAN KUAT TARIK BETON - Devi Oktarina; Olyvia Ayu P; Edi Purwanto (PROSIDING SNAST, 2018)
Concrete structurally has big compression strength, but it has weaknesses in lower tensile strength and fragile in nature. These weaknesses can be improved by adding steel fiber into concrete mixture evenly with random orientation. The objective of this research is to find out and study the influence of fiber fraction volume to the compression strength and tensile strength concrete. The objects to test consist of 24 fiber concrete cylinders with dimension of 150 mm x 300 mm for compression strength test and tensile strength. The fiber used local fiber (from steel wire with lf/df 60), with fiber fraction volume values of 0%; 0.2%; 0.4%; and 0.6% and the addition of 0.4% superplasticizer from cement weight for respective fraction volumes. Time testing done at the time when concrete was 28 days. The results showed that the addition of steel wire fiber in the concrete mixture reduced the level of workability of the concrete mixture. The statistic test results showed improvements of compression strength and tensile strength, of the fiber concrete fraction volume 0.4%. The increase of compression strength concete reached at the volume of 0.4 % fraction of 20,8132 % with the value of 33,40243 MPa and tensile strength concrete reached at the volume of 0.4 % faction of 3.24 % with the value of 2,9227 MPa.